Active Participation, Mind–Body Stabilization, and Coping Strategies with Integrative Medicine in Breast Cancer Patients - Theuser, Anna-Katharin; Antoniadis, Sophia; Langemann, Hanna; Wasner, Sonja; Grasruck, Katharina; Dietzel-Drentwett, Svenja; Fasching, Peter; Beckmann, Matthias; Hack, Carolin (Integrative Cancer Therapies, 2021)
Purpose: Increasing numbers of breast cancer survivors have led to a growing demand for integrative medicine. When patients have completed treatments associated with severe side effects, attention turns to reducing psychological symptoms, coping behavior, and self-care. The aim of this study was to assess patient-reported benefits in relation to active participation, mind–body stabilization, and coping strategies in breast cancer patients receiving integrative medicine. Methods: In a cross-sectional study, health counseling and treatment provided by a standardized integrative medicine consultancy service at the University Breast Center of Franconia were evaluated in 75 breast cancer patients over a 15-month period. At the baseline, the patients answered a questionnaire on their medical history, symptoms, and the treatment goals they were hoping to achieve with integrative medicine. Patient-reported outcomes relative to active participation, mind–body stabilization, and coping strategies were analyzed. Results: A large majority of the patients had previous experience with integrative medicine (91%). Most reported that they achieved their treatment goals with integrative medicine. Ninety-one percent achieved active participation in cancer treatment, 90% mind–body stabilization, and 79% improvement in coping strategies. Besides active participation, which was greatest in patients with stable disease, the success of integrative therapy was independent of age, concomitant diseases, previous integrative medicine experience, treatment state, and systemic cancer therapy. Conclusion: Breast cancer patients benefit from the counseling and treatment provided with integrative medicine in mind–body stabilization and coping with cancer. Active participation in cancer treatment is important for the patients. Integrative treatment services should form part of routine patient care.
CRIS-Team Scopus Importer:2021-03-19
Keywords: active participation; breast cancer; complementary and alternative medicine; coping; integrative medicine; mind–body; oncology

Cerebroplacental versus Umbilicocerebral Ratio—Analyzing the Predictive Value Regarding Adverse Perinatal Outcomes in Low- and High-Risk Fetuses at Term - Stumpfe, Florian; Mayr, Andreas; Schneider, Michael; Kehl, Sven; Stübs, Frederik; Antoniadis, Sophia; Titzmann, Adriana; Pontones, Constanza; Bayer, Christian M.; Beckmann, Matthias; Faschingbauer, Florian (Medicina, 2023)
Background and Objectives: The aim of this study was to investigate the prediction of adverse perinatal outcomes using the cerebroplacental (CPR) and umbilicocerebral (UCR) ratios in different cohorts of singleton pregnancies. Materials and Methods: In this retrospective cohort study, we established our own Multiple of Median (MoM) for CPR and UCR. The predictive value for both ratios was studied in the following outcome parameters: emergency cesarean delivery, operative intervention (OI), OI due to fetal distress, 5-min Apgar < 7, admission to neonatal intensive care unit, and composite adverse perinatal outcome. The performance of the ratios was assessed in the following cohorts: total cohort (delivery ≥ 37 + 0 weeks gestation, all birth weight centiles), low-risk cohort (delivery ≥ 37 + 0 weeks gestation, birth weight ≥ 10. centile), prolonged pregnancy cohort (delivery ≥ 41 + 0 weeks gestation, birth weight ≥ 10. centile) and small-for-gestational-age fetuses (delivery ≥ 37 + 0 weeks gestation, birth weight < 10. centile). The underlying reference values for MoM were estimated using quantile regression depending on gestational age. Prediction performance was evaluated using logistic regression models assessing the corresponding Brier score, combining discriminatory power and calibration. Results: Overall, 3326 cases were included. Across all cohorts, in the case of a significant association between a studied outcome parameter and CPR, there was an association with UCR, respectively. The Brier score showed only minimal differences for both ratios. Conclusions: Our study provides further evidence regarding predictive values of CPR and UCR. The results of our study suggest that reversal of CPR to UCR does not improve the prediction of adverse perinatal outcomes.
CRIS-Team Scopus Importer:2023-09-08
Keywords: cerebroplacental ratio; CPR; UCR; umbilicocerebral ratio

Comparison of methods for isolation and quantification of circulating cell-free DNA from patients with endometriosis - Hübner, Hanna; Lubrich, Hannah; Blum, Simon; Antoniadis, Sophia; Lermann, Johannes; Ekici, Arif Bülent; Fasching, Peter; Beckmann, Matthias; Rübner, Matthias; Burghaus, Stefanie (Reproductive Biomedicine Online, 2021)
Research question: Which is the optimal extraction method for isolating and quantifying circulating cell-free DNA (ccfDNA) from patients with endometriosis? Endometriosis is a common benign disease, associated with pain, infertility and reduced quality of life. Endometriosis is also a known risk factor for various cancers. Robust biomarkers for early detection and prediction of prognosis, however, are lacking. CcfDNA is an easy to obtain biomarker associated with prognosis of cancer patients and enables non-invasive analysis of somatic mutations. Recently, elevated levels of ccfDNA were detected in patients with endometriosis. Design: Two different ccfDNA extraction methods were compared: Maxwell RSC ccfDNA plasma kit (Maxwell) and QiAamp minElute ccfDNA mini kit (QIAamp). The ccfDNA and circulating mitochondrial DNA (mtDNA) quantities from 34 patients diagnosed with endometriosis were analysed. Fluorometric measurement and quantitative reverse transcription polymerase chain reaction (qRT-PCR) of short and long ALU and mtDNA fragments were used to quantiy ccfDNA. Results: The yield of ccfDNA isolated with the Maxwell method was significantly higher compared with the QIAamp method (P < 0.0001). Integrity of ccfDNA was significantly higher in the QIAamp isolate (P < 0.0001). Recovered mtDNA was not significantly different between both extraction methods used. Conclusions: The choice of extraction method can significantly influence the ccfDNA output and integrity. Both methods, however, enabled isolation of sufficient ccfDNA for further downstream applications. With this approach, isolation of ccfDNA could enable the non-invasive detection and analysis of somatic mutation within endometriosis tissue.
CRIS-Team Scopus Importer:2021-09-10
Keywords: CcfDNA; Circulating cell-free DNA; Endometriosis; Mitochondrial DNA; Plasma; Quantification

Comprehensive characterization of endometriosis patients and disease patterns in a large clinical cohort - Blum, Simon; Fasching, Peter; Hildebrandt, Thomas; Lermann, Johannes; Heindl, Felix; Born, Tilman; Lubrich, Hannah; Antoniadis, Sophia; Becker, Karina; Fahlbusch, Christine; Heusinger, Katharina; Burghaus, Stefanie; et al. (Archives of Gynecology and Obstetrics, 2021)
Purpose In many diseases, it is possible to classify a heterogeneous group into subgroups relative to tumor biology, genetic variations, or clinical and pathological features. No such classification is available for endometriosis. In our retrospective case-case analysis we defined subgroups of endometriosis patients relative to the type and location of the endometriosis lesion and relative to basic patient characteristics. Methods From June 2013 to July 2017, a total of 1576 patients with endometriosis diagnosed at surgery were included in this study. The patients' history and clinical data were documented using a web-based remote data entry system. To build subgroups, all possible combinations of endometriosis locations/types (peritoneal; ovarian endometriosis; deeply infiltrating endometriosis; adenomyosis) were used. Due to the variation in group sizes, they were combined into five substantial larger groups. Results Age, pregnancy rate, and live birth rate were identified as characteristics that significantly differed between the five patient groups that were defined. No significant differences were noted in relation to body mass index, length of menstrual cycle, age at menarche, reason for presentation, or educational level. Conclusion This study describes basic patient characteristics in relation to common clinical subgroups in a large clinical cohort of endometriosis patients. Epidemiological information about different clinical groups may be helpful in identifying groups with specific clinical courses, potentially suggesting novel approaches to early detection and to surgical and systemic treatment.
CRIS-Team WoS Importer:2021-09-10

Correction to: Introducing multiple-choice questions to promote learning for medical students: effect on exam performance in obstetrics and gynecology (Archives of Gynecology and Obstetrics, (2020), 302, 6, (1401-1406), 10.1007/s00404-020-05758-1) - Jud, Sebastian; Cupisti, Susanne; Frobenius, Wolfgang; Winkler, Andrea; Schultheis, Franziska; Antoniadis, Sophia; Beckmann, Matthias; Heindl, Felix (Archives of Gynecology and Obstetrics, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s00404-021-06112-9.
CRIS-Team Scopus Importer:2021-07-02

Functional Heterogeneity of Umbilical Cord Blood Monocyte-Derived Dendritic Cells - Schweiger, Petra; Hamann, Livia; Strobel, Julian; Weisbach, Volker; Wandersee, Alexandra; Christ, Julia; Kehl, Sven; Weidenthaler, Filip; Antoniadis, Sophia; Hackstein, Holger; Cunningham, Sarah (Journal of Immunology, 2024)
Human umbilical cord blood (UCB) represents a unique resource for hematopoietic stem cell transplantation for children and patients lacking suitable donors. UCB harbors a diverse set of leukocytes such as professional APCs, including monocytes, that could act as a novel source for cellular therapies. However, the immunological properties of UCB monocytes and monocyte-derived dendritic cells (MoDCs) are not fully characterized. In this study, we characterized the phenotype and functions of UCB-MoDCs to gauge their potential for future applications. UCB exhibited higher frequencies of platelets and lymphocytes as well as lower frequencies of neutrophils in comparison with adult whole blood. Leukocyte subset evaluation revealed significantly lower frequencies of granulocytes, NK cells, and CD14+CD16− monocytes. Surface marker evaluation revealed significantly lower rates of costimulatory molecules CD80 and CD83 while chemokine receptors CCR7 and CXCR4, as well as markers for Ag presentation, were similarly expressed. UCB-MoDCs were sensitive to TLR1–9 stimulation and presented quantitative differences in the release of proinflammatory cytokines. UCB-MoDCs presented functional CCR7-, CXCR4-, and CCR5-associated migratory behavior as well as adequate receptor- and micropinocytosis-mediated Ag uptake. When cocultured with allogeneic T lymphocytes, UCB-MoDCs induced weak CD4+ T lymphocyte proliferation, CD71 expression, and release of IFN-γ and IL-2. Taken together, UCB-MoDCs present potentially advantageous properties for future medical applications.<br

Individual dynamics of uterine natural killer cells in natural and stimulated cycles monitored using a new endometrial dating method - Alfer, Joachim; Fattahi, Amir; Bleisinger, Nathalie; Antoniadis, Sophia; Krieg, Jurgen; Dittrich, Ralf; Beckmann, Matthias; Hartmann, Arndt; Popovici, Roxana M.; Tremellen, Kelton (American Journal of Reproductive Immunology, 2022)
Problem It is important to evaluate the dynamics of uterine natural killer (uNK) cells in hormone replacement therapy (HRT) cycles, given their potential role in implantation and the common usage of HRT cycles with in vitro fertilization (IVF). Method of study A total of 132 subfertile patients were evaluated during the secretory phase of either natural ovulation (OV) or HRT cycles, with two biopsies taken on approximately days 5 and 10 after ovulation/progesterone administration in a single menstrual cycle. Immunohistochemical Personal Endometrial Maturation Analysis (PEMA) was used to better quantify secretory-phase endometrial development, in combination with subsequent evaluation of uNK cell density. Results uNK cell density increased rapidly from the early to mid-secretory phase, with mean uNK densities of 113 and 117 per mm(2) in first biopsies and 315 and 387 per mm(2) in second biopsies for OV and HRT cycles, respectively. After reassessment of endometrial development with PEMA, the first and second biopsies in HRT and OV cycles were histologically dated to developmental ranges between days 15-20 (first biopsy) and days 19-25 (second biopsy). Conclusion Subfertile women showed variable endometrial development in PEMA assessment, with uNK cell density correlating with the dating results. Overall, comparable levels of uNK cell density were observed in OV and HRT cycles. Importantly, uNK cell density depends on the histological maturation stage, with similar low coefficients of determination. This observation suggests that aberrant uNK cell results more likely reflect displaced endometrial maturation, rather than an intrinsic anomaly in uNK cell trafficking.
CRIS-Team WoS Importer:2022-09-30

Influence of mindfulness-based Stress Reduction on Patients with Endometriosis in a randomized Cohort Study - Antoniadis, Sophia; Burghaus, Stefanie; Becker, Karina; Beckmann, Matthias; Hack, Caroline (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Introducing multiple-choice questions to promote learning for medical students: effect on exam performance in obstetrics and gynecology - Jud, Sebastian; Cupisti, Susanne; Frobenius, Wolfgang; Winkler, Andrea; Schultheis, Franziska; Antoniadis, Sophia; Beckmann, Matthias; Heindl, Felix (Archives of Gynecology and Obstetrics, 2020)
Purpose: Testing is required in medical education. The large number of exams that students face requires effective learning strategies. Various methods of improving knowledge retention and recall have been discussed, two of the most widely evaluated of which are test-enhanced learning and pause procedures. This study investigated the effect of voluntary multiple-choice questions on students’ performance. Methods: In a prospective study from April 2013 to March 2015, 721 students were randomly assigned to receive supplementary online material only (control group) or additional multiple-choice questions (investigative group) accompanying lectures. Their performance in the final exam was evaluated. Results: A total of 675 students were ultimately included, with 299 randomly assigned to the investigative group and 376 to the control group. Students in the investigative group scored significantly better in relation to grades and points (2.11 vs. 2.49; 33 vs 31.31; p < 0.05). The effect declined over time. Conclusion: This is the first study of the use of voluntary multiple-choice questions to improve medical students’ performance. The results support test-enhanced learning and the feasibility of implementing multiple-choice questions in lectures.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Gynecology; Lecture; Multiple choice; Obstetrics; Teaching; Testing

Lack of evidence for effects of lockdowns on stillbirth rates during the SARS-CoV-2 pandemic in Bavaria: analysis of the Bavarian perinatal survey from 2010 to 2020 - Stumpfe, Florian; Schneider, Michael; Antoniadis, Sophia; Mayr, Andreas; Fleckenstein, Tobias; Staerk, Christian; Kehl, Sven; Hermanek, Peter; Boehm, Julian; Scharl, Anton; Beckmann, Matthias; Hein, Alexander (Archives of Gynecology and Obstetrics, 2022)
Background: Internationally, potential effects of national SARS-CoV-2-related lockdowns on stillbirth rates have been reported, but data for Germany, including risk factors for fetal pregnancy outcome, are lacking. The aim of this study is to compare the stillbirth rates during the two first lockdown periods in 2020 with previous years from 2010 to 2019 in a large Bavarian cohort. Methods: This study is a secondary analysis of the Bavarian perinatal data from 2010 to 2020, including 349,245 births. Univariate and multivariable regression analyses were performed to investigate the effect of two Bavarian lockdowns on the stillbirth rate in 2020 compared to the corresponding periods from 2010 to 2019. Results: During the first lockdown, the stillbirth rate was significantly higher compared to the reference period (4.04 vs. 3.03 stillbirths per 1000 births; P = 0.03). After adjustment for seasonal and long-term trends, this effect can no longer be observed (P = 0.2). During the second lockdown, the stillbirth rate did not differ in univariate (3.46 vs. 2.93 stillbirths per 1000 births; P = 0.22) as well as in multivariable analyses (P = 0.68), compared to the years 2010 to 2019. Conclusion: After adjustment for known long-term effects, in this study we did not find evidence that the two Bavarian lockdowns had an effect on the rate of stillbirths.
CRIS-Team Scopus Importer:2022-11-25
Keywords: COVID-19; Stillbirths; Stillborn

Patterns and Trends of Herbal Medicine Use among Patients with Gynecologic Cancer - Theuser, Anna Katharin; Hack, Carolin; Fasching, Peter; Antoniadis, Sophia; Grasruck, Katharina; Wasner, Sonja; Knoll, Stefanie; Sievers, Hartwig; Beckmann, Matthias; Thiel, Falk C. (Geburtshilfe und Frauenheilkunde, 2021)
Background More and more information about complementary and integrative medicine is becoming available, especially among cancer patients. However, little is known about the use of herbal medicine by patients with gynecologic cancers. This study aimed to assess the use of herbal products by gynecologic cancer patients compared with healthy controls. Methods This cross-sectional study was conducted at the Department for Gynecology and Obstetrics of Erlangen University Hospital and included 201 patients with gynecologic cancer and 212 healthy controls. Use of herbal medicines was evaluated using a standardized questionnaire. Medical information on cancer patients was collected from hospital records. Group comparisons were done using a logistic regression model. Risk ratios were assessed using a Poisson regression model. Results Gynecologic cancer patients used herbal medicine significantly less often than healthy persons. 69% of gynecologic cancer patients and 81% of healthy participants reported using herbal products. 40% of cancer patients and 56% of healthy persons reported using plants for medicinal purposes. Motives of cancer patients for using herbal medicine included treatment of cancer-related symptoms. The major source of information for both groups was family and friends. Conclusions Although herbal medicine was used less by patients with gynecologic cancer, herbal products were used by both cancer patients and healthy individuals. To provide cancer patients with optimal therapy, oncologists should be informed about the herbal products used by their patients as this will allow them to take their patients' self-medication with herbal medicine into account. Counseling by oncologists on the use of herbal medicine should be encouraged.
CRIS-Team Scopus Importer:2021-07-02
Keywords: cancer; complementary and alternative medicine; gynecologic oncology; herbal medicine; integrative medicine

Results of Stimulation Treatment through pulsatile GnRH Substitution by using an innovative, patient-controlled System (LutrePulse((R))) - Hildebrandt, Thomas; Lotz, Laura; Blum, Simon; Fahlbusch, C.; Heusinger, K.; Cupisti, S.; Dittrich, Ralf; Beckmann, Matthias; Antoniadis, Sophia (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Veranstaltungsbericht: 10. Wissenschaftliches Symposium der AGO-TraFo - Banys-Paluchowski, Malgorzata; Antoniadis, Sophia; Hein, Alexander; Fehm, Tanja N.; Arnold, Norbert; Fasching, Peter (Geburtshilfe und Frauenheilkunde, 2018)
CRIS-Team Scopus Importer:2021-07-19